Bureaucratic Pathology of Social Aid Services in Sragi Village Pekalongan Regency - Nova Shella Rida Az-zahra; Hendri Hermawan Adinugraha (Al-Muamalah: Jurnal Ekonomi Islam, Filantropi dan Perbankan Syariah, 2024)
This research aims to analyze the performance of government bureaucracy in the distribution of social assistance in Sragi Village, Pekalongan Regency. Through a qualitative approach with a case study, this research identifies various issues in the distribution of social assistance, including the inability to determine the right targets, distribution delays, lack of transparency, and accountability. Data were obtained through direct observation and analysis of community conversations.The results of the research show that the inability to distribute accurately and the delay in distributing social assistance are caused by various factors, such as inefficiency in bureaucracy, technical issues, and lack of transparency. Although no acts of corruption or abuse of authority were found, the integrity and responsibility of employees in carrying out their duties are crucial to maintaining public trust. The conclusion emphasizes the need for improvements in the social assistance distribution system, including increasing efficiency, transparency, and integrity in bureaucracy, as well as emphasizing employee responsibility. By addressing these various aspects, it is hoped that the social assistance distribution process can become more effective and efficient, with a greater impact on the communities in need.